A recurrent F8 mutation (c.6046C>T) causing hemophilia A in 8% of northern Italian patients: evidence for a founder effect. Issue 2 (14th December 2015) - Garagiola, Isabella; Seregni, Sabrina; Mortarino, Mimosa; Mancuso, Maria Elisa; Fasulo, Maria Rosaria; Notarangelo, Lucia Dora; Peyvandi, Flora
Abstract: Hemophilia A is a heterogeneous hemorrhagic disorder caused by a large number of mutations. Recurrent mutations are rare, except intron 22 and intron 1 inversions. The substitution of a cytosine to a thymine at nucleotide 6046 in F8 gene was identified in a group of Italian patients affected by hemophilia A from a specific region of Northern Italy with a prevalence of 7.6%. This F8 variant was the second most frequent mutation in our cohort, after the intron 22 inversion. The identification of the same mutation in a restricted population gets to suppose the existence of a founder effect. Intragenic and extragenic polymorphic markers were tested to assess this assumption. A peculiar haplotype in linkage disequilibrium with this recurrent mutation (c.6046C>T) was identified in 71% of patients, supporting a founder effect. This distinctive haplotype was not identified in a control group (Fisher's exact test, P  < 0.0001), coming from the same geographic region. These data strongly suggested the presence of a founder effect, supporting the existence of a single mutation event. Using DMLE+2.3 software and the mathematical approach described by Bengtsson and Thomson, the inferred age of this mutation is supposed to be about 2325 years (95% CI: 904–5081) ago. Abstract : Among 300 hemophilia A Italian patients screened for F8 gene mutations, a recurrent mutation (c.6046C>T) was identified in a group of patients from a specific region of Northern Italy with a prevalence of 7.6%. This F8 variant was the second most frequent mutation in our cohort, after the intron 22 inversion. A haplotype analysis was performed to investigate the existence of a founder effect associated to the recurrent mutation. The data obtained from haplotype analysis strongly suggested the presence of a founder effect, supporting the existence of a single mutation event. Using DMLE+ software and a mathematical approach, we also estimated the age of this mutation.